ST. PETER AND ST. PAUL IN ROME: THE PROBLEM OF THE MEMORIA APOSTOLORUM AD CATACUMBAS - Chadwick, Henry (The journal of theological studies, 1957)
H. CHADWICK; ST. PETER AND ST. PAUL IN ROME: THE PROBLEM OF THE MEMORIA APOSTOLORUM AD CATACUMBAS, The Journal of Theological Studies, Volume VIII, Issue 1, 1 A